A Relevance-Theoretic Approach To The Analysis Of Phonesthemes In Selected English Novels And Their Translation Into Persian - Tirani, Mohammad Jamshid (2019)
The present research studies phonesthemes in English novels and their translation into Persian from Relevance Theory point of view. Phonesthemes are submorphemic segments that bear associated attributes which are same or different than the arbitrary meaning of the word they appear in. The target phonestheme in the present study is /gl/ meaning ‘light’ in words such as ‘glitter’. Since phonesthemes have been studied rarely in the context of novels and seldom in the context of translating novels, the main focus of this study is phonesthemes in English novels and how they are translated into Persian. The data of this study are collected from three novels of Charles Dickens namely ‘A Christmas Carol’, ‘Great Expectations’, and ‘Oliver Twist’. In analyzing data, the main notions of Relevance Theory i.e. ‘processing effort’ and ‘contextual effects’ are applied to describe how phonesthemes function in novels and how they are translated into Persian. In order to fulfill the objectives of the study, a qualitative research method is adopted specifically with the three steps of data collection and analysis provided by Grounded Theory. The results of the analysis of the data demonstrated that Relevance Theory provides a sound description of the phonesthemes both in Source Texts and Target Texts as well as the process of translation. The results also provide a novel insight into the phenomenon of phonesthemes in literary texts, especially novels, and practical techniques of translating them that can enhance the appreciation of artistic values in literary texts and their recreation in Target Texts.